3-D impact angle constrained distributed cooperative guidance for maneuvering targets without angular-rate measurements. (September 2018) - Wang, Xiang Hua; Tan, Chee Pin
Abstract: In this paper, a three-dimensional (3-D) distributed cooperative guidance scheme is presented for multiple missiles to attack a single maneuvering target at pre-specified impact angles. A finite time observer is firstly proposed to provide accurate estimates of full states and disturbances; this is particularly crucial since some system states are not available as they are dependent on the unknown acceleration of the target. Then the guidance law is designed, which consists of two parts: the individual part and cooperative part. In the individual part, each missile is designed separately such that it will fly along the desired line of sight (LOS) after a given time which ensures hit-to-kill attack for the maneuvering target at the desired impact angles. In the cooperative part, the guidance law is designed for each missile using only information from adjacent missiles, to make all missiles hit the target at the same time. Hence it is ensured that all missiles can hit the target simultaneously, as well as at the desired directions (impact angles), then successfully achieving salvo attack. Finally, simulations are performed to verify the effectiveness of the proposed scheme. Highlights: Firstly, the simultaneous attack considered in this paper happens in the 3-D space. A distributed guidance for maneuvering target without LOS angular rate is proposed. The proposed scheme ensures a simultaneous attack from different directions.